Noncovalently D-arabinitol Molecularly Imprinted Polymers (MIPs) to Identify Different Sugar Alcohols - Yuni Retnaningtyas; Ganden Supriyanto; Roedi Irawan; Siswandono Siswodihardjo (مجلة بغداد للعلوم, 2021)
Molecularly imprinted polymers (MIPs) are an effective method for separating enantiomeric compounds. The main objective of this research is to synthesize D-arabinitol MIPs, which can selectively separate                  D-arabinitol and its potential application to differentiate it from its enantiomer compound through a non-covalent approach. A macroporous polymer was synthesized using D-arabinitol as a template, acrylamide as a functional monomer, ethylene glycol dimethacrylate (EGDMA) being a cross-linker, dimethylsulfoxide (DMSO) being a porogen, as well as benzoyl peroxide being an initiator. After polymer synthesis,                  D-arabinitol was removed by a mixture of methanol and acetic acid (4:1, v/v). Fourier-Transform Infrared spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM) distinguished the MIPs and NIPs.                     A selectivity test of MIPs against its enantiomers (L-arabinitol, xylitol, adonitol, and glucose) was carried out using the batch rebinding method. The binding site was quantitatively determined using the Langmuir equation. The results of the selectivity test showed that the MIPs produced was quite selective toward its enantiomer and could potentially be used to separate D-arabinitol from its enantiomer.